2021
DOI: 10.1523/jneurosci.1828-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Visual Cues Modulates Their Representation in Mouse Visual and Cingulate Cortex

Abstract: Choosing an action in response to visual cues relies on cognitive processes, such as perception, evaluation, and prediction, which can modulate visual representations even at early processing stages. In the mouse, it is challenging to isolate cognitive modulations of sensory signals because concurrent overt behavior patterns, such as locomotion, can also have brainwide influences. To address this challenge, we designed a task, in which head-fixed mice had to evaluate one of two visual cues. While their global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 98 publications
1
10
0
Order By: Relevance
“…The anterior motor areas covered by timescale-specific ICs are involved in planning and decision making (Svoboda and Li 2018;Inagaki et al 2022;Xu et al 2022;Yin et al 2022). The visual areas and posterior parietal regions are critical for both vision and sensory-motor integration (Beloozerova and Sirota 2003;Freedman and Ibos 2018;Steinmetz et al 2019;Wal et al 2021).…”
Section: Timescale-specific Ics Reveal Flexibility In Cortical Segmen...mentioning
confidence: 99%
“…The anterior motor areas covered by timescale-specific ICs are involved in planning and decision making (Svoboda and Li 2018;Inagaki et al 2022;Xu et al 2022;Yin et al 2022). The visual areas and posterior parietal regions are critical for both vision and sensory-motor integration (Beloozerova and Sirota 2003;Freedman and Ibos 2018;Steinmetz et al 2019;Wal et al 2021).…”
Section: Timescale-specific Ics Reveal Flexibility In Cortical Segmen...mentioning
confidence: 99%
“…An excellent example of balance between ecological validity and variable control is the research carried out by Wal et al ( 2021 ). Authors investigated how behavioral demands could influence the selectivity to visual stimuli of cortical neurons.…”
Section: Moving Toward Ecological Modelsmentioning
confidence: 99%
“…This highlights the importance of noting the animal's internal state in how the brain processes such visual stimuli. In this sense, Wal et al ( 2021 ) presented two visual cues that provided equivalent stimulation to V1 neuron's RF. Their experiment showed that neuronal activity in response to the two cues was equivalent without a rewarding context.…”
Section: Challenging Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the role of the mPFC in learning sensorimotor associations, the mPFC exhibits sensory responses specifically to stimuli that are behaviorally relevant (Bichot et al, 1996;Wal et al, 2021). These stimuli can be of any modality including visual (Orsolic et al, 2021;Peters et al, 2021;Reinert et al, 2021), auditory (Moorman and Aston-Jones, 2015;Pinto and Dan, 2015), somatosensory (Le Merre et al, 2018), and even multisensory (Coen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%